Partitioning behavior of natural radionuclides during combustion of coal in thermal power plants. Issue 1 (2nd January 2017) - Sahu, S. K.; Tiwari, M.; Bhangare, R. C.; Ajmal, P. Y.; Pandit, G. G.
ABSTRACT: Coal-fired power generation produces huge amounts of fly ash and bottom ash of different properties. Coal contains many naturally occurring radionuclides, which on burning are enriched in the ashes; their discharge to the environment may cause significant exposure of the public to this technologically enhanced naturally occurring radioactive material. Most of these nuclides tend to become particle bound and hence are adsorbed on the ash particles. It is thus important to assess the behavior of radionuclides under combustion in the particle phase. To study the behavior of radionuclides in the particle phase, i.e., in combusted coal ashes, radioactivity measurement of coal and ash samples from different power plants was carried out using alpha and γ-ray spectrometry. The activity of 210 Po in fly ash ranged from 12.6 to 91.3 Bq kg −1, while the range of activity concentrations of 238 U, 226 Ra, 232 Th, 40 K in fly ash were 56.1–133, 44.3–119, 9.3–144, and 34.5–221 Bq kg −1, respectively. Partitioning behavior of the radionuclides, their relative enrichment factors, and effect of particle size on enrichment of the nuclides in fly ash were also studied. Radionuclides were also grouped using their relative enrichment factors, a consequence of their volatile nature. A good correlation between the partitioning behavior, volatility, and relative enrichment factors of the radionuclides was observed in this study. This outcome of the study could be very useful for determining the fate of the radionuclides, from the bulk low-concentration mineral state in coal mines to the high-concentration particle phase of ashes after burning in power plants. This is important since it is the higher concentration of radionuclides in the particle phase that is a potential source of exposure to the public.